The genus Cyperus (Cyperaceae) in Rio Grande do Norte State, Brazil - Ribeiro,André Rodolfo de Oliveira (2015)
Abstract Cyperus is a Pantropical genus and the second richest in species in Cyperaceae. It encompasses about 550 species worldwide, with about 100 of these occurring in Brazil. Studies on the taxonomy of this genus are scarce and punctual in Brazil. In this study, the occurrence of species was surveyed through 27 collecting expeditions across different regions in the state of Rio Grande do Norte and analyzis of specimens of several herbaria. Twenty four species of Cyperus were identified, including six new occurrences and one new species, here described, but that will be properly published in other work. This study includes a dichotomous key for the identification of the species, as well as illustrations, descriptions, taxonomic comments and geographical distribution.